PENGARUH KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK SUTURE & GLOVES PADA PT. SURGIKA ALKESINDO MEDAN - Marwan Jhon Erixson Sinaga; Ardian Pandiangan (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2020)
The object of this research is PT. Surgika Alkesindo Medan. Some problems that occur at PT. Surgika Alkesindo Medan namely the quality of the products offered is not in accordance with the desires of consumers and also the price of the products offered is less affordable because it is relatively expensive and not in accordance with the quality of the products provided and promotions made to Suture Gloves products are still less effective and efficient and tend to monotonous. Increasing product quality and reducing prices and increasing promotions are expected to improve consumer purchasing decisions. Theories used in this research are theories related to product quality, price and promotion. This research uses a quantitative approach and the type of research is quantitative descriptive. Data collection methods are done by interview, questionnaire and study documentation. The data analysis method used is multiple linear regression analysis. The population is the average of all consumers who make purchases on Suture Gloves products at least once at PT. Surgika Alkesindo Medan, amounting to 127 consumers. Determination of the sample in this study using random sampling with a sample withdrawal using the formula Slovin 95% obtained as many as 96 respondents of the study sample. The results of the hypothesis show that product quality, price and promotion simultaneously or partially have a significant effect on purchasing decisions and price is the most dominant factor influencing purchase decisions. Determination test results, namely Adjusted R Square of 0.523 means that 52.3% of the purchase decision variable can be explained by variables of product quality, price and promotion.The conclusions in this study are simultaneously and partially the quality of products, prices and promotions have   a   positive   and   significant   effect   on   purchasing   decisions   at   PT.   Surgika   Alkesindo   Medan.